Multifunctional 2D- Materials: Gallium Selenide. (2017) - Singh, Narsingh B.; Hua Su, Ching; Arnold, Bradley; Choa, Fow-Sen; Sova, Stacey; Cooper, Christopher
Abstract: There is tremendous need for the 2D graphene-like single and multiple layered materials since they can be very useful as multifunctional materials for electronic, optical and energy generation and storage applications. We describe the preparation and morphology of selenide crystals and compared with wrinkled graphene which we had grown by annealing method. The characterization of observed standing fibrous film indicates behavior like graphene. Compositional analysis of graphene showed traces of oxygen impurities in some cases. Thermal analysis showed that material was stable up to 400C. However, some morphological changes were observed at high temperature. We studied an important multifunctional semiconductor material Gases for exploring 2D-characteristics and compare with graphene. The class of GaSe materials are highly anisotropic and in many cases, involve covalent and Van der Wall forces making processing very difficult. We will describe results of highly anisotropic gallium selenides, and thallium gallium selenide crystals which have been investigated for nonlinear optical and THz applications. GaSe has strong tendency of cleaving due to Van der Waal forces along –C direction making 2D materials possible. Very thin (smaller than 500 mm) GaSe was fabricated and optically characterized. The material was free from oxygen and water, and does not have any sign of hygroscopic nature indicating GaSe a very good alternate material. GaSe sheet showed very low absorption coefficient in their transparency region. Transmission and Raman studies near cut-off wavelength were performed to understand the defect in the material.